Integrated assessment of multilevel biomarker responses and chemical analysis in Mussels from Sao Sebastiao, São Paulo, Brazil - Pereira, Camilo Dias Seabra; Abessa, Denis Moledo de Souza; Bainy, Afonso Celso Dias; Zaroni, Leticia Pires; Gasparro, Marcia Regina; Bicego, Marcia Caruso; Taniguchi, Satie; Furley, Tatiana Heid; de Sousa, Eduinetty Ceci Pereira Moreira (Society Environmental Toxicology & Chemistry-setac, 2007)
The aim of the present study was to investigate the presence of contaminants in the mussel Perna perna from Sao Sebastiao Channel, São Paulo, Brazil, and to evaluate the effects of these contaminants on these organisms at biochemical (catalase [CAT], glutathione-S-transferase [GST], and cholinesterase [ChE]), cellular (neutral red retention time [NRRT] assay), and physiological (cardiac monitoring) levels. Two sampling surveys were performed (winter of 2001 and summer of 2002) at six stations along the channel: Cigarras, station 1; late Clube de Ilhabela, station 2; Oil Terminal, station 3; Toque Toque, station 4; Ponta da Sela, station 5 (reference station); and Taubate, station 6. Differences in CAT activity were observed between mussels from stations 3 and 5 during the winter, but no differences were detected in the summer. No differences in GST activity were found among stations during the winter, although animals from station 3 showed higher activity during the summer. The ChE activity was significantly higher in the mussels from stations I and 2 during the winter and from stations I and 3 during the summer. Organisms from stations I through 4 showed statistically lower NRRT in both seasons. Similar heart rates were observed in the mussels from all stations. Hydrocarbons were detected in organisms from all the stations in both seasons. During the winter, higher polycyclic aromatic hydrocarbon (PAH) levels were observed in organisms from station 3, whereas during the summer, higher levels of metals were found in organisms from stations 1, 3, and 4. The multivariate analyses showed a strong influence of PAHs on the winter biological results, but metals showed higher influence on these responses in the summer, indicating multiple contaminant sources.
Keywords: biomarkers; mussels; Sao Sebastiao channel; marine pollution; environmental assessment